1992
DOI: 10.1161/01.cir.85.2.497
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex sensitivity and heredity in essential hypertension.

Abstract: BACKGROUND Abnormalities in baroreflex control of heart rate may be important in the pathogenesis of essential hypertension. METHODS AND RESULTS To investigate the influence of heredity on baroreflex function, we measured baroreflex sensitivity in 40 untreated patients with essential hypertension grouped by the presence (FH+) or absence (FH-) of a family history of hypertension and in 24 normotensive counterparts. Baroreflex sensitivity was assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
87
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(101 citation statements)
references
References 64 publications
12
87
0
2
Order By: Relevance
“…35 Xing-Sheng et al 31 concluded from human genetic studies that polymorphism of the eNOS gene results in reduced eNOS activity, indicating a depressant effect of eNOS-generated NO on baroreflex sensitivity. Based on the observation that Bj-PRO-10c induced production of NO in neuronal cells from postnatal whole-SHR-brain cell culture, we analyzed the gene expression levels of ASS, eNOS and nNOS, which are known to be involved in NO synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…35 Xing-Sheng et al 31 concluded from human genetic studies that polymorphism of the eNOS gene results in reduced eNOS activity, indicating a depressant effect of eNOS-generated NO on baroreflex sensitivity. Based on the observation that Bj-PRO-10c induced production of NO in neuronal cells from postnatal whole-SHR-brain cell culture, we analyzed the gene expression levels of ASS, eNOS and nNOS, which are known to be involved in NO synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Most evidence suggests that BRS is partly influenced by genetic factors [4], and indeed previously identified polymorphisms seem to explain part of the variance in BRS [30,31]. However, until now only one study reported on the heritability of BRS, in that case obtained from 5-min measurements during a rest condition [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a poor understanding of the determinants of spontaneous BRS. Impaired BRS in hypertensive patients has been suggested to be in part genetically determined [4]. The relative contribution of genetic influences to individual variation in BRS can be estimated in a twin design.…”
Section: Introductionmentioning
confidence: 99%
“…16,24 We have previously shown hypertension family history to influence such potentially pathogenic traits as baroreceptor slope 24 or the cardiac response to alpha 2 -adrenergic blockade. 16 Such early phenotypic responses, occurring in at-risk subjects even before the onset of hypertension, may qualify as more informative 'intermediate phenotypes' 1,2,16 in the genetic analysis of this complex trait.…”
Section: Heredity: Family History Of Hypertensionmentioning
confidence: 99%